การประยุกต์ใช้งานโปรแกรมการเชื่อมต่อภาพสำหรับภาพถ่ายเอกซเรย์แบบระยะยาว - แก้วเหล็ก, ฐิติพงศ์ (Science Essence Journal, 2017)
บทคัดย่อ การถ่ายภาพเอกซเรย์แบบระยะยาวเป็นการถ่ายภาพสำหรับการวินิจฉัยรอยโรคในการตรวจกระดูกระยะยาว เช่น กระดูกสันหลัง และรยางค์ เทคนิคเชื่อมภาพเป็นเทคโนโลยีสร้างภาพที่ใช้สำหรับการเอกซเรย์แบบระยะยาว ภาพกระดูก 2 หรือ 3 ภาพ ถูกเชื่อมต่อกันโดยใช้โปรแกรมของผู้ผลิตที่ติดตั้งมาในเครื่องถ่ายภาพ โปรแกรมนี้มีราคาแพง การศึกษานี้จึงนำเสนอการประยุกต์ใช้โปรแกรมเชื่อมภาพ (Image Composite Editor) เพื่อการเชื่อมต่อภาพกระดูกขาระยะยาว ภาพเอกซเรย์แบบระยะยาวที่สร้างจากโปรแกรม แบบมี และไม่มีอุปกรณ์บอกระยะบนภาพถูกนำมาทดสอบ ภาพเอกซเรย์กระดูกขาที่แบ่ง 3 ส่วน ถูกประมวลผลด้วยวิธีการเริ่มต้นของโปรแกรม และวิธีการอื่นถูกเทียบกัน วิธีการเหล่านี้ ประกอบด้วย แบบอัตโนมัติ เคลื่อนที่บนระนาบ เคลื่อนที่บนระนาบแบบเบ้ เคลื่อนที่บนระนาบแบบทัศนมิติ และเคลื่อนที่แบบหมุน พบว่าในภาพกลุ่มไม่มีอุปกรณ์บอกระยะ ที่ใช้วิธีการเคลื่อนที่บนระนาบแบบเบ้ เคลื่อนที่บนระนาบแบบทัศนมิติ และเคลื่อนที่แบบหมุน เกิดการผิดรูป ขณะที่กลุ่มภาพกลุ่มมีอุปกรณ์บอกระยะ ทุกวิธีการเชื่อมต่อภาพได้ผลโดยไม่เกิดการผิดรูป โปรไฟล์แนวตั้งและแนวนอนของภาพทั้ง 2 กลุ่ม ขยายด้านล่างและขวาของภาพ โดยเฉพาะวิธีการเคลื่อนที่แบบหมุน วิธีการอัตโนมัติและเคลื่อนที่บนระนาบมีคุณภาพสูงใกล้เคียงกับภาพต้นฉบับ สรุปว่าโปรแกรมสามารถเชื่อมต่อภาพได้ถูกต้องสูงในภาพที่มีอุปกรณ์บอกระยะ - - - ABSTRACT Long-length radiography is an imaging for the diagnosis of lesions in long bone examinations such as spine and extremity. The image stitching technique is the imaging technology used for long-length x-rays. Two or three contiguous images of the bone are stitched together by a manufacturer provided program embedded in the imaging equipment. This program is expensive. In our study, we proposed the application of an image stitching program (Image Composite Editor), to stitch long leg radiographic together. Long-length radiographic produced by the program, with and without a ruler on the image, was examined. The three separate parts of the leg radiography were processed using the default technique of the program, and the other techniques were compared. These techniques included automatic, planar motion, planar motion with skew, planar motion with perspective, and the rotation motion method. It was observed that, in the non-ruler based image groups the images produced by the planar motion with skew, the planar motion with perspective, and the rotation motion techniques, were distorted, while for the ruler based image groups, all techniques effectively stitched the images together without distortion. The vertical and horizontal profile of the two image groups were expanded in the lower and right sides of the images, especially in the rotation motion technique. The automatic and planar motion technique images were of a high quality similar to that of the initial image. Conclusion is that the program can produce high accurate stitched images for ruler based radiography.